DEM/FEM simulation of the shot peening process on sharp notches. (15th August 2021) - Marini, M.; Fontanari, V.; Benedetti, M.
Highlights: Discrete element modeling of the shot peening process on sharp notches. Dynamic explicit finite element modeling of the shots impacts. The notch residual stress (RS) field is compared with experimental measures. The RS generation mechanisms is highly localized at the notch tip. Abstract: The residual stress field produced by shot peening on Al-7075-T651 prismatic samples carrying V-edge notches is evaluated through combined Discrete Element Modeling (DEM) and Finite Element Modeling (FEM) simulations. Special care is paid to faithfully model the interaction between peening nozzle, shots and notched target through DEM analyses and to understand the coverage level at the notch root. The simulated stream of shots with randomly distributed size, location and velocity is imported into an explicit dynamic FE model of a neighborhood of the notch tip. The resulting residual stress (RS) field is compared to the RS field computed using thermal fields in a FEM simulation, calibrated with experimental data collected through Micro-hole Drilling, Micro-slot Cutting and Micro-X-ray Diffraction techniques. The obtained results are in good agreement with experimentally reconstructed RS and suggests the hypothesis that the notch tip RS field is dictated only by impacts occurring in the very vicinity of the notch apex. Graphical abstract: Image, graphical abstract